Knowledge Diplomacy: What Are the Key Characteristics? - Knight, Jane (International Higher Education, 2020)
Knowledge diplomacy is a new approach to understanding the role of international higher education, research, and innovation in strengthening relations among countries and addressing common global challenges. This article examines the key characteristics of the knowledge diplomacy approach—collaboration, reciprocity, and mutuality—and provides examples of how higher education and research can contribute to international relations and help to address global issues.